Rounding function-based zero crossing detection for a sensorless BLDC motor control - Gujja, Musa Mohammed; Ishak, Dahaman; Hamidi, Muhammad Najwan; Salem, Mohamed; Abdullah, Mohamad Nazir; Alluhaybi, Khalil (Institute of Advanced Engineering and Science, 2025)
Permanent magnet brushless DC (PMBLDC) motors are favored for their low maintenance, high reliability, and efficiency, making them ideal for industrial, domestic, military, aerospace, and robotics applications. Sensor less control is the most preferred technique for PMBLDC motors due to its reliability and cost-effectiveness, eliminating the need for physical sensors. A crucial aspect of sensor less control is accurately detecting the point of zero crossing of the back electromotive force (BEMF) signals. Traditional methods, such as rotor position estimation, input observers, and AI-based strategies, can suffer from high ripples and computational inefficiencies. This paper introduces an approach using the rounding function to determine the point of zero crossing, aiming to enhance precision and reduce computational overhead. The rounding function converts continuous BEMF signals into discrete signals, minimizing ripples and facilitating accurate zero-crossing detection. This method improves detection accuracy while simplifying computation demands. Validation was performed through a MATLAB Simulink simulation and an experiment using the F28379D microcontroller, gate driver, and a six-switch inverter. The results demonstrate the effectiveness of the proposed approach, showing agreement between experimental and simulation outcomes.